Pengaruh Keadilan Prosedural Terhadap Penganggaran Partisipatif Melalui Komitmen Organisasi - Andry Arifian Rachman (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
This study aims to examine: (1) the influence of procedural fairness to participative budgeting; and (2) the influence of procedural fairness to participative budgeting through organization commitment.The purpose of descriptive research method used in this study is to obtain a description of the characteristics of the variables and then verification is applied to determine the relationships between variables through hypothesis testing. The population in this research is 165 officers in 55 Local Government Unit Agencies (SKPDs) in West Java Province. Validity and reliability of questionnaires are tested before examining the hypotheses. Structural Equation Modeling (SEM) is used as the analysis technique in this research.The research findings are as follows: (1) procedural fairness hasa positive effect on the participative budgeting; and (2) procedural fairness has a positive effect on the participative budgeting through organization commitment.